(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study assessed the efficiency of Azadirachta indica (Neem) leaf powder (NLP) and its activated carbon (NLAC) as potential adsorbents for the extraction of benzene and toluene from simulated refinery wastewater. The objective is to evaluate the capacity of these materials to enhance the quality of industrial effluents and assist developing nations in attaining the Sustainable Development Goals (SDGs), specifically Goal 6 (Clean water and Sanitation), Goal 12 (Responsible Consumption and Production), and Goal 15 (Life on Land). Azadirachta indica leaf powder and its activated carbon were prepared by air-drying Azadirachta indica leaf in the shade at room temperature (25 °C) for 72 hr, followed by oven drying at 105 °C for 30 min until they were crisp, and chemical activation with phosphoric acid. The adsorbents were assessed by Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET) analysis. The FTIR analysis identified the functional groups in the adsorbent that are accountable for the adsorption property. The surface presents a fibrous composition including irregular macropores and enlarged cavities that may facilitate the diffusion of adsorbate molecules through the macropores. The batch adsorption process was studied under numerous conditions, encompassing varying concentrations, pH, contact time, adsorbent amount, and temperature. The findings indicated that activated carbon derived from Neem leaf, possessing a surface area of 427.154 m²/g, exhibited substantial adsorption of benzene and toluene, attaining removal efficiency of 74 % and 81 % respectively, under optimal conditions of (pH 10, contact time 75 min, adsorbent dosage 1 g,...